PENGARUH PENGGUNAAN PASIR MALANG SEBAGAI FILTER DALAM MEDIA AIR LIMBAH BATIK TERHADAP KELANGSUNGAN HIDUP IKAN KOI (Cyprinus carpio Linn) - Noviana Viadolo R.L; Hadi Pranggono; M Bahrus Syakirin (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
Batik Indonesia became more famous after gaining recognition from the United Nations Edutional, Scientific and Cultural Organization (UNESCO). Batik-making is certainly generate waste and pollution , many batik industry that drain effluent wastewater to flow - the flow of water around, causing the flow of polluted water, declining water quality and damage aquatic life (fish, microorganisms , and others). Water is an important medium in the operational activities of aquaculture , this is because the water functions as the survival of fish . The use of poor sand as a filter in an aqueous medium batik waste koi care also determine the effect the survival of fish in the media proficiency level with the treatment of poor sand different, and knowing the poor sand capable of being a substrate that is able to purify water because it has a composition of CaO , Al2O3 and FeO. In testing the media by way of poor sand substrate put the aquarium bottom (sedimentation), clearly visible color change that occurs at the beginning of batik waste water colored dark red to green translucent (for 5 -day precipitation) . Treatment with the best survival percentage in C is 86.76 % (800 g) and D (1000 g) percentage of 93.33 % , while in treatment A (control) fish dying and treatment D percentage of fish life is very low at 13 , 33 % with poor sand 600gr . The test results stated poor sand able to be purifying (demineralization) water.Keywords : poor sand, batik waste water, koi fish